Audit of Readiness in Aviation Industry Airport Standards on Airport Poprad-Tatry - Jančík, Filip; Kupec, Václav; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Nowadays, aviation is one the most crucial parts of world transportation ecosystem and are influenced by unprecedented turbulent era caused by rapid technological advancements, changing global policies. Every day the people and cargo pass through most important part ofaviation, airports, and they must adapt quickly to any change and are nerve centers. This audit will focus mainly on aviation industry airport standards and Readiness in Aviation Industry Airport Standards on Airport Poprad-Tatry. Main aim of thus audit will be assessment and visualization of long-term trends and evaluation of preparedness to new upcoming policies and regulations. In the form of methodology, risk assessment will analyze all critical parts, visualization will help to showcase results, giving overall perspective image. This approach supports all actions will are based on audit of readiness on Airport Poprad-Tatry, key findings include not only strengths but also weaknesses and their assessment. Based on this inside, recommendation will be tailored to fit Airport Poprad-Tatry to target all gaps. In conclusion, this will help any future development of robust future ready projects and infrastructure. Proactive adaptation will be beneficial not only for operations but also for future competitive edge in its region.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses